The physiology and impact on fertility of the period of proestrus in lactating dairy cows - Wiltbank, M. C. (2014)
In cattle, proestrus begins with the initiation of luteolysis and ends with initiation of estrus and the GnRH/LH surge. This period is marked by a dramatic decrease in circulating progesterone (P4) that reaches a nadir by about 36-48 h in cows undergoing natural or prostaglandin F2 alpha (PGF)-induced luteolysis. Inadequate luteolysis is a cause of reduced fertility particularly in timed AI programs with small elevations in circulating P4 reducing fertility. Increasing circulating estradiol (E2) during proestrus is dependent on presence, size, and function of the dominant follicle and this varies during natural proestrus, due to whether animals have two or three follicular waves, and during PGF-induced proestrus, according to stage of the follicular wave at time of PGF treatment. Inadequate circulating E2 can limit fertility and increase pregnancy loss in some specific circumstances such as in cows with low BCS and in cows during heat stress. Thus, studies to optimize the length of proestrus and the concentrations of E2 and P4 during proestrus could produce substantial improvements in fertility and reductions in pregnancy loss.